Domestic explosions: Low intensity and high impact - Utsav Anand Mani; Rajesh Ursekar; Elizabeth Sada; Digvijay Dhananjay Adake; Vikram Sarangan; Sushma Vijaykumar Shriyan; Pushpraj Singh (Indian Journal of Burns, 2024)
Explosions seen at home are rare and should be taken seriously by manufacturing companies and the society. Home is regarded as a safe sanctuary, and accidents in the safety at home should not be overlooked or unreported. We would like to report six cases due to the explosion of a cell phone, an air conditioning compressor, an electric meter, and a steam geyser. All the patients survived; however, one suffered serious long-term morbidity. Case reports on explosions due to appliances are rare. Growing dependency on such appliances ensures that such cases would be more commonly seen in the future or are commonly seen but less reported in medical journals. Raising awareness about this topic in the scientific community and mainstreaming this etiology of trauma may serve some purpose in the future.